2018
DOI: 10.1016/j.agee.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

On-farm evaluation and determination of sources of variability of soybean response to Bradyrhizobium inoculation and phosphorus fertilizer in northern Ghana

Abstract: HighlightsInoculation increased grain yield over the control by 24%.Combined application of P + I increased grain yield over the control by 37%.Soil and environmental factors explained up to 79% of yield variation.Agronomic index for responsiveness was robust than economic index.About 53% of the farmers that applied inoculant had VCR of ≥2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
5
31
0
Order By: Relevance
“…The increase in grain yield with P fertilizer and rhizobium inoculant supports earlier findings that the combined application of P with rhizobium inoculant increased grain yield and nitrogenase activity as well as enhanced soil fertility (Fatima et al, 2007). Similarly, a study by Ulzen et al (2018) reported significantly higher soybean grain yields from plots that received P and/or inoculation than those of the control plots. Accordingly, Ndakidemi and Semoka (2006) recommended that, for farmers who can afford P fertilization, its combined use with inoculants can further increase grain yield.…”
Section: Growth Yield and Yield Componentsmentioning
confidence: 84%
“…The increase in grain yield with P fertilizer and rhizobium inoculant supports earlier findings that the combined application of P with rhizobium inoculant increased grain yield and nitrogenase activity as well as enhanced soil fertility (Fatima et al, 2007). Similarly, a study by Ulzen et al (2018) reported significantly higher soybean grain yields from plots that received P and/or inoculation than those of the control plots. Accordingly, Ndakidemi and Semoka (2006) recommended that, for farmers who can afford P fertilization, its combined use with inoculants can further increase grain yield.…”
Section: Growth Yield and Yield Componentsmentioning
confidence: 84%
“…In 2018 there are 16 articles that fit these criteria, including 44 , which reports on the agronomic findings of the soybean trials used for the current paper. Supplementary Table S1 online summarizes information for those 16 articles 44,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] relating to the 5 possible sources of discrepancies, and documents that these are indeed common practices in recently published research. Column 3 shows that random selection of farmers is the exception, and also shows that many papers don't specify selection criteria (discrepancy 4).…”
Section: Calculation Of the Returns Of The Input Packages The Value-mentioning
confidence: 99%
“…Soybean in SSA also suffers from large yield gaps and low productivity [30,35,36]. Globally, average soybean yields near 2.5 metric tons per hectare [37], while the small producers that dominate soybean production in sub-Saharan agriculture achieve yields of around 0.8 metric tons, or onethird the yield [38,39].…”
Section: Soy and Maize In Sub-saharan Africamentioning
confidence: 99%
“…Afterwards, seeds are lightly covered with loose soil, taking precaution not to pack soil on top of seed too tightly. If possible, inoculant should be added to the soybean seeds prior to sowing to improve performance and fixation of nitrogen ( [30,36]; Awuni et al 2020).…”
Section: A Practical Overview Of Soy-maize Rotation In Sub-mentioning
confidence: 99%